THE REVITALISATION OF THERMAL AREAS IN THE BAGNOLI DISTRICT (NAPLES) AS A CHANCE FOR TOURISM DEVELOPMENT IN THE CAMPANIA REGION IN THE CONTEXT OF SELECTED EUROPEAN EXPERIENCES - Noviello, Monika; Smętkiewicz, Karolina (Quaestiones Geographicae, 2019)
The article presents the project of revitalisation of the former industrial zone of the district of Bagnoli in the context of possibilities of development of the thermal tourism in the Italian region of Campania. The authors refer primarily to the thermal facilities which were in use in the period from the second half of the 18th century to the 1970s, and which border directly the area of revitalisation, but weren’t included in the plan. The aims of the article are: (1) the reconstruction and the recommendation of the locations of the forgotten thermal sites formerly in use in the area of the Bagnoli district, (2) the presentation of the current state and development of such buildings, (3) the estimation of the tourism development potential in the region with reference to similar experiences of Poland and Austria, where the thermal infrastructures became the driving force of socio-economic development.